Contribution of GPS and GIS in the Study of the Dynamics of the Coastline and the Mouth of the Moulouya (Northeast Morocco) - Sbai Abdelkader; Mouadili Omar; Benrbia Khadija; Hlal Mohammed; Amghar Ahmed (E3S Web of Conferences)
This study assesses the utility of Global Positioning System (GPS) data in monitoring coastal dynamics, focusing on the Moulouya estuary. The research demonstrates the capability of GPS in capturing 3D estuarine kinematics with annual temporal resolution and sub-centimetre accuracy. Analysis of GPS data collected from 2013 to 2021 reveals both spatial and temporal variations in the Moulouya estuary's dynamics. The findings emphasize GPS's ability to continuously track the kinematics of geomorphological features exhibiting small, gradual displacements. Moreover, the study underscores GPS's potential to complement traditional topometric methods, enhancing coastal monitoring and warning systems.